2021
DOI: 10.1111/cas.14942
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular permeability in cancer metastasis

Abstract: Enhancement of vascular permeability is indispensable for cancer metastasis. Weakened endothelial barrier function enhances vascular permeability. Circulating tumor cells moving in the microvasculature tend to invade into stromal tissue at the location where vascular permeability is enhanced. Many basic studies have identified permeability factors by using gene‐modified animals and cells. These factors directly/indirectly interact with endothelial cells. Here, we review vascular permeability factors and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 64 publications
(147 reference statements)
1
28
0
Order By: Relevance
“…The co-culture medium effectively recruited macrophages, demonstrating a potential mechanism of angiogenesis. Furthermore, vascular endothelial permeability was increased by fibrinogen in vitro, consistent with previous study [36][37][38]. We found that ICAM1 expression was induced by exogenous fibrinogen.…”
Section: Discussionsupporting
confidence: 92%
“…The co-culture medium effectively recruited macrophages, demonstrating a potential mechanism of angiogenesis. Furthermore, vascular endothelial permeability was increased by fibrinogen in vitro, consistent with previous study [36][37][38]. We found that ICAM1 expression was induced by exogenous fibrinogen.…”
Section: Discussionsupporting
confidence: 92%
“…261 In addition, vascular inflammation caused by adipokines like leptin leads to elevated permeability, which is indispensable for cancer metastasis. 262 , 263 Finally, adipocytes can affect the biological behavior of carcinoma by modifying the extracellular matrix (ECM) structure which is characterized by a high degree of fibrosis in ATME. 264 Typically, the researchers observed an abundant fibrotic response in tumor areas that were enriched in adipocytes or located adjacent to adipose tissue.…”
Section: The Developmental Origin and Anatomical Location Of Thermoge...mentioning
confidence: 99%
“…Tumor cells can bind to endothelial cells and induce EC necrosis via a TNF receptor family mechanism. Tumor cells can also release a large number of molecules that affect EC permeability [ 35 ].…”
Section: Vascular Permeability In Diseasesmentioning
confidence: 99%